Cistorraphy in a dog after car trauma: Case report - Sousa Lima, Antonio; Nunes Rodrigues, Ivanilce; Costa Lima, Wagner; Anunciação Silva Dantas Lima, Dayanne; Soares Lima, Larissa Fernanda; Costa Lima, Sérgio Henrique; Rodrigues Barbosa, Vanessa; Boechat, Yuri luiz (Pubvet, 2021)
The urinary system of dogs and cats can be affected by several pathologies, of which one of the most frequent is the rupture of the urinary vesicle, which can be caused by several factors, which highlights the traumatic ones as more frequent, as a result of the extravasation from the urine to the cavity. Several clinical signs are observed, and when untreated, as well as the primary cause, they can lead the patient to death. The diagnosis for this disease ranges from physical exams to complementary exams and has cistorraphy as the definitive treatment. The present work reports a case of a bladder rupture in a dog caused by automobile trauma, the patient in question after the accident, was seen at a private clinic, where he was diagnosed with such a disease through physical examinations, then he was referred to the hospital university veterinarian at the Federal University of Piauí to undergo the cistorraphy surgical procedure, all procedures adopted as well as the surgeon's experience were of great importance for the recovery of the patient, who is now fully recovered.
Keywords: Bladder; dog; rupture; surgical procedure